Influência da natureza do suporte sobre a atividade do carbeto de molibdênio promovido por níquel na reação de reforma seca do metano - Silva, Camila Gabriele (2019)
Al2O3, SiO2 and SiC supported molybdenum carbides promoted by nickel were evaluated in the dry reforming of methane (DRM) at 800 °C. Several oxide precursors were synthesized and carburized using temperature-programmed carburization (TPC). The precursors and catalysts were characterized by X-ray diffraction (XRD), temperature-programmed carburization (TPC), N2 physisorption, scanning electron microscopy (SEM), thermogravimetric analysis and Raman spectroscopy. The increase in Ni content led to increased activity, showing that the ideal Ni/Mo atomic ratio for nickelsupported β-Mo2C catalysts supported on alumina should be in the range 2<Ni/Mo<3, and for supported on silica in the range of 3<Ni/Mo<4. As for carburizing temperature it has been shown that as it increases, the formation of carbon on the surface increases. SiC supported catalysts were active and stable under the conditions tested independently of Ni/Mo ratio and carburizing temperature showing the superiority of this support and its versatility when faced with different reaction conditions.